Quorum quenching altered microbial diversity and activity of anaerobic membrane bioreactor (AnMBR) and enhanced methane generation - Liu, Jianbo (2022)
A facultative bacterium Microbacterium sp. (QQ strain) was found significantly mitigated membrane biofouling and also increased methane production. It was found genera Nitrospira, norank-c-Bacterodetes vadinHA17, Trichococcus and family Anaerolineaceae were likely responsible for membrane biofouling. The presence of QQ strain increased the total abundance of fermentative and acetogenic genera by 0.61% and 379.61%, respectively, but had a minor effect on the abundance of methanogens. The increased methane production was likely due to the strengthened methanogenic activity and more available substrates. Homo-acetogenic Treponema was enriched (9.01%) in the presence of QQ strain suggesting that apart from hydrogenotrophic methanogenic pathway, extra CH4 could be also produced from the additional acetate synthesized via homo-acetogenic pathway. This study advances knowledge about the effects of QQ strain on microbial communities, microbiota biofouling behavior and anaerobic fermentation process in AnMBRs.